Production of antagonistic substance by Eikenella corrodens isolated from the oral cavity of human beings with and without periodontal disease - Apolônio, A.C.M; Carvalho, M.A.R; Ribas, R.N.R; Sousa-Gaia, L.G; Santos, K.V; Lana, M.A; Nicoli, J.R; Farias, L.M (Journal of applied microbiology, 2007)
Antagonistic abilities may confer ecological advantages for micro-organisms in competitive ecosystems. However, reports regarding this phenomenon in Eikenella corrodens are not available. Nineteen E. corrodens strains, isolated from the oral cavity of human beings without periodontal disease (n = 5) and with aggressive (n = 9) and chronic (n = 5) periodontitis, as well as a reference strain (E. corrodens ATCC23834), were evaluated for antagonistic activity. The following indicators were used: Porphyromonas gingivalis FDC381, Prevotella intermedia ATCC25611, Actinomyces israelii ATCC12102, Eubacterium lentum ATCC25559, Peptostreptococcus anaerobius ATCC27337, Actinobacillus actinomycetemcomitans FDCY4, Fusobacterium nucleatum ATCC10953, Streptococcus sanguinis ATCC10557, Streptococcus uberis ATCC9927, Streptococcus mutans IM/UFRJ, Staphylococcus aureus ATCC33591 and Candida albicans ATCC18804. All the strains showed antagonism against at least one of the indicator strains. This phenomenon was more frequently observed for strains isolated from patients with chronic periodontitis (36·4%), than those from healthy subjects (20·6%) and those with aggressive periodontitis (10·8%). The heterogeneous antagonistic spectrum exhibited by E. corrodens isolates suggests their ability to produce more than one antagonistic substance, whose ecological relevance is yet to be demonstrated. This is the first description of antagonistic compound production by E. corrodens and its relationships with the clinical status of the patients.